Utilizing surface modification in plasma‐enhanced cyclic etching of tantalum nitride to surpass lithographic limits. Issue 9 (2nd April 2019) - Marchack, Nathan; Hernandez, Keith; Walusiak, Benjamin; Innocent‐Dolor, Jon‐l; Engelmann, Sebastian
Abstract: Pitch subdivision of tantalum nitride (TaN) lines is demonstrated across a 200 mm wafer using a cyclic quasi‐atomic layer etch process in an inductively coupled plasma reactor. Chlorine (Cl2 ) and hydrogen (H 2 ) chemistries are introduced sequentially to an argon plasma in discrete steps to etch the TaN film. The starting lithographic pattern with critical dimension (CD) of approximately 82 nm and pitch of 200 nm thus yields lines of approximately 40 nm CD and 100 nm pitch with minimal line edge roughness increase. We identify a synergistic effect between H 2 ‐exposed TaN and Cl 2 plasma as contributing to this result, as well as a potential link to surface oxidation. Optical emission spectroscopy analysis of the plasma discharge is used to characterize reactive species densities and explain the observed changes in profile. Abstract : Pitch multiplication of tantalum nitride (TaN) line/space patterns is demonstrated using a plasma‐enhanced Cl 2 ‐based cyclic etch process. Modification of the surface through H 2 exposure and surface oxidation from mask materials are examined as facilitating factors. Cyclic quasi‐ALE (q‐ALE) processes show great potential for surpassing the limits of conventional plasma etching due to the tunability of discrete reactions.